Homopolymer tail-mediated ligation PCR: a streamlined and highly efficient method for DNA cloning and library construction. (January 2013) - Lazinski, David W.; Camilli, Andrew
The amplification of DNA fragments, cloned between user-defined 5′ and 3′ end sequences, is a prerequisite step in the use of many current applications including massively parallel sequencing (MPS). Here we describe an improved method, called homopolymer tail-mediated ligation PCR (HTML-PCR), that requires very little starting template, minimal hands-on effort, is cost-effective, and is suited for use in high-throughput and robotic methodologies. HTML-PCR starts with the addition of homopolymer tails of controlled lengths to the 3′ termini of a double-stranded genomic template. The homopolymer tails enable the annealing-assisted ligation of a hybrid oligonucleotide to the template's recessed 5′ ends. The hybrid oligonucleotide has a user-defined sequence at its 5′ end. This primer, together with a second primer composed of a longer region complementary to the homopolymer tail and fused to a second 5′ user-defined sequence, are used in a PCR reaction to generate the final product. The user-defined sequences can be varied to enable compatibility with a wide variety of downstream applications. We demonstrate our new method by constructing MPS libraries starting from nanogram and sub-nanogram quantities of Vibrio cholerae and Streptococcus pneumoniae genomic DNA.